2015
DOI: 10.3325/cmj.2015.56.230
|View full text |Cite
|
Sign up to set email alerts
|

Cultural inter-population differences do not reflect biological distances: an example of interdisciplinary analysis of populations from Eastern Adriatic coast

Abstract: AimTo compare the population group from the Šopot graveyard with population groups from traditional Croatian medieval graveyards by using anthropological, craniometrics, and mitochondrial (mtDNA) analysis and to examine if the cultural differences between population groups reflect biological differences.MethodsWe determined sex, age at death, pathological, and traumatic changes of skeletal remains from the Šopot graveyard and compared them with a cumulative medieval sample from the same region. We also perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, even though it achieved relatively high classification accuracy for females (85%), it is not at that extent important for sex estimation as it is significant for population affinity. This topic has been covered in the previous study that showed a strong association between genetic markup and cranial measurements ( 37 ). Thus, it additionally supports the application of developed functions on the modern sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even though it achieved relatively high classification accuracy for females (85%), it is not at that extent important for sex estimation as it is significant for population affinity. This topic has been covered in the previous study that showed a strong association between genetic markup and cranial measurements ( 37 ). Thus, it additionally supports the application of developed functions on the modern sample.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where pelvis was not preserved or morphological indicators were not consistent, we conducted an analysis of ancient DNA, ie, amelogenin locus using previously described protocol (12,35-37). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 108 graves were on the edges of the burial site, with the remaining seven graves being found further north and forming the second group. These burials can be dated to the early ninth century and are described as the oldest burial horizon, mainly consisting of single graves [22][23][24][25]. A male from Grave 63 belonged to the first burial group and was buried in a wooden coffin with no grave goods.…”
Section: Archaeological Settingmentioning
confidence: 99%
“…На формирование уровня здоровья населения различных территорий оказывает влияние комплекс факторов: социальных, географических, экологических и др [1,3,9,11,14,17]. Отдельные группы населения могут отличаться друг от друга особенностями состояния здоровья даже в пределах сравнительно ограниченной территории [1,2,5,7,12,26].…”
Section: Introductionunclassified